Analysis of Health Workers' Professionality in Improving Service Quality - Apriyaldi Monoarfa; Lindanur Sipatu; Rosida Adam; Arie kurniawan (Al-Qalam Institue, 2025)
This study aims to explore the influence of hospital service quality on patient satisfaction at Ampana Regional Hospital, focusing on the role of healthcare professionals in improving this quality. Using a qualitative case study design, this study analyzed the five SERVQUAL dimensions reliability, responsiveness, assurance, empathy, and tangibles that influence patient satisfaction in the inpatient ward. Data were collected through in-depth interviews with ten informants and participant observation. The results showed that services at Ampana Regional Hospital generally met patient expectations, particularly in terms of reliability and responsiveness. However, there were still shortcomings in initial communication regarding hospital facilities and a lack of written information, such as leaflets. This study also highlighted the importance of therapeutic communication and empathetic care in improving patient satisfaction. Practical implications of this study include the importance of hospitals maintaining facility quality and improving communication to enhance the patient experience. At the same Time, theoretically, it strengthens the SERVQUAL model in the context of hospital services.